2000
DOI: 10.1007/bf02946103
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods for the determination of aflatoxins in various food matrices at concentrations regarding the limits set in european regulations: development, characteristics, limits

Abstract: Methods for the determination of aflatoxins in paprika, peanut butter, pistachio paste, fig paste and baby food were developed. The methods employ an immunoaffinity cleanup step and reversed-phase liquid chromatography. All steps of the analysis were tested for their suitability for all matrices with focus on method robustness, simplicity, toxicology, environment, and user friendliness. Extraction procedures, chromatographic separation and post column derivatisation techniques were elaborated for this purpose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…An example of this process was the optimization of the analytical method for aflatoxins in commodities and at levels of importance for EU legislation, which led to the investigation of the influence of mobile phase composition on the separation of AFB 1 , AFB 2 , AFG 1 and AFG 2 (Stroka et al, 2000b). It was found that mixtures of water and methanol led to broad peaks and long retention times, whereas water-acetonitrile mixtures could not achieve baseline resolution of all four aflatoxin analogues.…”
Section: High-performance Liquid Chromatography Columns and Mobile Phmentioning
confidence: 98%
See 2 more Smart Citations
“…An example of this process was the optimization of the analytical method for aflatoxins in commodities and at levels of importance for EU legislation, which led to the investigation of the influence of mobile phase composition on the separation of AFB 1 , AFB 2 , AFG 1 and AFG 2 (Stroka et al, 2000b). It was found that mixtures of water and methanol led to broad peaks and long retention times, whereas water-acetonitrile mixtures could not achieve baseline resolution of all four aflatoxin analogues.…”
Section: High-performance Liquid Chromatography Columns and Mobile Phmentioning
confidence: 98%
“…However, the iodination method also has several disadvantages, including the need for a separate pump and a heated reaction coil, which can cause peak broadening, and the possible crystallization of iodine in incorrectly operated systems. Consequently, reaction systems utilizing the more reactive halogen, bromine, were developed with the added advantage of a greater analyte response than achieved with iodine (Stroka et al, 2000b;O'Riordan and Wilkinson, 2009). Post-column bromination can be cleanly accomplished in either one of two ways, the simplest being electrochemical generation in a so-called Kobra cell.…”
Section: Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years significant improvements have been introduced in the analysis of aflatoxins especially in column chromatography technology [19,22]. The use of packing materials with particle sizes <2 m and the use of chromatographs that can support very high pressures led to a dramatic reduction of analysis times.…”
Section: Introductionmentioning
confidence: 99%
“…Although separation can be achieved with both normal and reversed phase columns, reversedphase systems are more commonly used. The optimum mobile phase was found to be a ternary mixture, composed of water, methanol and acetonitrile, tailored to the individual characteristics of the HPLC column [19].…”
Section: Introductionmentioning
confidence: 99%